2022
DOI: 10.3390/pharmaceutics14071394
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of Somatostatin Receptors in Various Neoplasms: A Systematic Review

Abstract: Somatostatin receptors (SSTR) are expressed in various neoplasms and can be targeted for both diagnostics as well as therapeutics. This systematic review aims to compile and discuss the prevalence of somatostatin receptor expression in various neoplasms. We performed a literature search from Google Scholar and PubMed using relevant keywords to look for all publicly available data regarding SSTR expression in various cancers. Both histopathological and radiographical studies were included for SSTR assessment. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The findings of positive expression of SST2 and/or SST3 in various solid tumors observed in our study are in concordance with previously published data, indicating that various human cancerous tissues exhibit SST expression, including GEP-NET, lymphoma, gastrointestinal carcinoma, head and neck carcinoma, lung carcinoma, Merkel cell carcinoma, malignant melanoma, meningioma, neuroblastoma, thyroid carcinoma, thymoma, breast carcinoma, pheochromocytoma, paraganglioma, prostate carcinoma, ovarian carcinoma, and endometrial carcinoma, as recently reviewed by Priyadarshini et al 11 . Remarkably, some tumor types have been reported to express SST3 at similar levels or higher than SST2A (some GEP-NETs, thyroid carcinoma, thymoma, breast cancer, ovarian tumors, pheochromocytomas, and specially nonfunctioning pituitary tumors) 51 60 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of positive expression of SST2 and/or SST3 in various solid tumors observed in our study are in concordance with previously published data, indicating that various human cancerous tissues exhibit SST expression, including GEP-NET, lymphoma, gastrointestinal carcinoma, head and neck carcinoma, lung carcinoma, Merkel cell carcinoma, malignant melanoma, meningioma, neuroblastoma, thyroid carcinoma, thymoma, breast carcinoma, pheochromocytoma, paraganglioma, prostate carcinoma, ovarian carcinoma, and endometrial carcinoma, as recently reviewed by Priyadarshini et al 11 . Remarkably, some tumor types have been reported to express SST3 at similar levels or higher than SST2A (some GEP-NETs, thyroid carcinoma, thymoma, breast cancer, ovarian tumors, pheochromocytomas, and specially nonfunctioning pituitary tumors) 51 60 .…”
Section: Discussionsupporting
confidence: 93%
“…Much work has been performed and published on the expression of SSTs in human malignancies, including a body of IHC work using various protocols 11 , 26 . Investigating the correlation of SST2 immunohistochemical scoring versus PET scans of [ 68 Ga]Ga-DOTATATE tracer in GEP-NET patients, Yu et al 34 found that the highest sensitivity and specificity of IRS in predicting the imaging results were obtained when defining the positivity cutoff value as 6, meaning that 51–80% of the tumor cells should be moderately stained or 10–50% should be strongly stained.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of the triazole heterocycle into the peptide backbone was accomplished by a diazotransfer reaction (general procedure 3) followed by the CuAAC reaction (general procedure 4) with the corresponding α-amino alkynes (for complete synthesis and characterization, see Supplementary Materials, pp. [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The peptide was elongated until completion of the DOTA-containing sequence and the cleavage, cyclization and full deprotection were performed in accordance with general procedure 5.…”
Section: Synthesismentioning
confidence: 99%
“…SST-14 exerts inhibitory and antisecretory actions by interacting with a group of G-protein-coupled receptors (GPCRs) comprising five subtypes (somatostatin receptor subtype 1–5, SST 1-5 R) [ 2 ]. The SST 1-5 R are expressed in various tissues and organs serving diverse regulatory functions, but they are also of significant importance in oncology by virtue of their high-density expression in different tumors [ 3 , 4 ]. Thus, neuroendocrine tumors (NETs), such as growth hormone-secreting pituitary adenoma, predominantly express SST 2 R, but concomitant expression of different subtypes is a common finding, as for example, in breast cancer [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Somatostatin receptors (SSTRs) are expressed in several normal tissues (such as the pancreas and the gastrointestinal tract), as well as in a number of neoplasms, including PanNETs [6,7] The overexpression of SSTRs in PanNETs has been utilized in the diagnostics and management of patients with a PanNET since the development of SSTR-targeted imaging and therapeutic options [6,[8][9][10]. There are some reports on the immunohistochemical analysis of SSTR expression in insulinomas [11][12][13][14], but to the best of our knowledge, no previous studies have evaluated all the SSTRs with novel monoclonal antibodies.…”
Section: Introductionmentioning
confidence: 99%